Cover Feature: Single‐Round DNA Aptamer Selection by Combined Use of Capillary Electrophoresis and Next Generation Sequencing: An Aptaomics Approach for Identifying Unique Functional Protein‐Binding DNA Aptamers (Chem. Eur. J. 39/2021). Issue 39 (15th June 2021) - Saito, Shingo; Sakamoto, Toshiki; Tanaka, Naoki; Watanabe, Ryo; Kamimura, Takuya; Ota, Kazuki; Riley, Kathryn R.; Yoshimoto, Keitaro; Tasaki‐Handa, Yuiko; Shibukawa, Masami
Abstract : "DNA Aptaomics" is reported in this work for finding functional DNA aptamers by a semi‐comprehensive and quantitative single‐round selection using capillary electrophoresis and next generation sequencing according to a selection rule based on analogous sequences. By mining sequence data obtained from sub‐libraries with different DNA conformations, structure‐induced (FRET type) aptamers for thrombin were reasonably selected for the first time. More information can be found in the Full Paper by S. Saito et al. (DOI: 10.1002/chem.202100177 ).